Smart Technologies and Corporate Sustainability (International Journal of Food and Nutritional Sciences, 2022)
The relationship among smart technology and business responsibility is the topic of this article. The goal of this article is to investigate the function of business environmental agenda in regulating the relationship among intelligent technology and sustainable performance. The findings reveal that business initiative completely mediators the relationship among technological solutions and economic protection, as well as intelligent technology and societal conservation, based on surveys of 280 SMEs. Furthermore, technological solutions have a substantial impact on socioeconomic environmental, although this link is moderated in part by company renewable energy goals. Intelligent technology has no immediate impact on societal or ecological protection. This technique also aids in the reduction of wastage by guaranteeing that food is preserved in the best possible shape.